Interpretasi Imam Al-Maraghi dan Ibnu Katsir Terhadap Qs. Ali Imran Ayat 190-191: Imam Al-Maraghi and Ibn Kathir's Interpretation of Qs. Ali Imran Verses 190-191 - Wida Nafila Sofia (Tafkir: Interdisciplinary Journal of Islamic Education, 2021)
This paper is stimulated by the fact that education is an activity that is deliberately carried out to actualize all the potential of students, both in the affective, cognitive and psychomotor domains, both soul (nafs), heart (qalb) and intellectual ('aql). The reality that has happened is that the education system has only been able to produce weak people, with the characteristics of low initiative and creativity, low self-confidence, helplessness and ultimately unable to be independent. In the Al-Qur'an, there are many verses that call on people to pay attention to, reflect on and compose Allah, whether in the heavens, the earth or among. Among the verses that explain this are Q.S Ali Imran verses 190-191. Data obtained through literature studies from several books and journals that explain Al-Maraghi and Ibn Kathir's interpretation of QS. Ali Imran 190-191 as the focus of discussion. This research reveals that as human beings we must always remember Allah SWT and also measure what Allah SWT has created so that we can take a response. This also requires the integration of the function of reason and dhikr as a unity that must be present in every Muslim, in order to be able to take lessons from the signs of the power of Allah SWT.